Long-term Follow-up and Safety of Patients after an Upfront Therapy with Letrozole for Early Breast Cancer in Routine Clinical Care – The PreFace Study - Hack, Carolin; Maass, Nicolai; Aktas, Bahriye; Kümmel, Sherko; Thomssen, Christoph; Wolf, Christopher; Kolberg, Hans Christian; Brucker, Cosima; Janni, Wolfgang; Dall, Peter; Schneeweiss, Andreas; Marme, Frederik; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Introduction Adjuvant treatment of patients with early-stage breast cancer (BC) should include an aromatase inhibitor (AI). Especially patients with a high recurrence risk might benefit from an upfront therapy with an AI for a minimum of five years. Nevertheless, not much is known about the patient selection for this population in clinical practice. Therefore, this study analyzed the prognosis and patient characteristics of postmenopausal patients selected for a five-year upfront letrozole therapy. Patients and Methods From 2009 to 2011, 3529 patients were enrolled into the adjuvant phase IV PreFace clinical trial (NCT01908556). Postmenopausal hormone receptor-positive BC patients, for whom an upfront five-year therapy with letrozole (2.5 mg/day) was indicated, were eligible. Disease-free survival (DFS), overall survival (OS) and safety in relation to patient and tumor characteristics were assessed. Results 3297 patients started letrozole therapy. The majority of patients (n = 1639, 57%) completed the five-year treatment. 34.5% of patients continued with endocrine therapy after the mandated five-year endocrine treatment. Five-year DFS rates were 89% (95% CI: 88-90%) and five-year OS rates were 95% (95% CI: 94-96%). In subgroup analyses, DFS rates were 83%, 84% and 78% for patients with node-positive disease, G3 tumor grading, and pT3 tumors respectively. The main adverse events (any grade) were pain and hot flushes (66.8% and 18.3% of patients). Conclusions The risk profile of postmenopausal BC patients selected for a five-year upfront letrozole therapy showed a moderate recurrence and death risk. However, in subgroups with unfavorable risk factors, prognosis warrants an improvement, which might be achieved with novel targeted therapies.
CRIS-Team Scopus Importer:2024-12-16
Keywords: aromatase inhibitors; early breast cancer; hormone therapy; letrozole; prognosis

Prognostic impact of selection criteria of current adjuvant endocrine therapy trials NATALEE and monarchE in postmenopausal HRpos/HER2neg breast cancer patients treated with upfront letrozole - Fasching, Peter; Hack, Carolin; Nabieva, Naiba; Maass, Nicolai; Aktas, Bahriye; Kümmel, Sherko; Thomssen, Christoph; Wolf, Christopher; Kolberg, Hans Christian; Brucker, Cosima; Janni, Wolfgang; Dall, Peter; et al. (European Journal of Cancer, 2024)
Background: The monarchE and NATALEE trials demonstrated the benefit of CDK4/6 inhibitor (CDK4/6i) therapy in adjuvant breast cancer (BC) treatment. Patient selection, based on clinical characteristics, delineated those at high (monarchE) and high/intermediate recurrence risk (NATALEE). This study employed a historical patient cohort to describe the proportion and prognosis of patients eligible for adjuvant CDK4/6i trials. Methods: Between 2009 and 2011, 3529 patients were enrolled in the adjuvant PreFace clinical trial (NCT01908556). Eligibility criteria included postmenopausal patients with hormone receptor-positive (HRpos) BC for whom a five-year upfront therapy with letrozole was indicated. Patients were categorized into prognostic groups according to monarchE and NATALEE inclusion criteria, and their invasive disease-free survival (iDFS) and overall survival (OS) were assessed. Results: Among 2891 HRpos patients, 384 (13.3 %) met the primary monarchE inclusion criteria. The majority (n = 261) qualified due to having ≥ 4 positive lymph nodes. For NATALEE, 915 out of 2886 patients (31.7 %) met the eligibility criteria, with 126 patients (13.7 %) being node-negative. Patients from monarchE with ≥ 4 positive lymph nodes and NATALEE with stage III BC exhibited the poorest prognosis (3-year iDFS rate 0.87). Patients ineligible for the trials demonstrated prognoses similar to the most favorable patient groups within the eligibility criteria. Conclusion: Patient populations eligible for monarchE and NATALEE trials differed. Nearly a third of the postmenopausal HRpos population, previously under upfront letrozole treatment, met the NATALEE prognostic eligibility criteria. As certain eligible groups had a prognosis similar to non-eligible patients, it might be interesting to explore additional patient groups for CDK4/6i therapy.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Aromatase inhibitors; CDK4/6 inhibitors; Early breast cancer; Hormone therapy; Letrozole; Prognosis